Implementing an intervention to enhance care delivery and consistency for people with hip fracture and cognitive impairment in acute hospital wards: a mixed methods process evaluation of a randomised controlled feasibility trial (PERFECTED) - Chris Fox; Fiona Poland; Bridget Penhale; Simon P Hammond; Jane L Cross; Tamara Backhouse; Vicki McDermott-Thompson (BMJ Open, 2023)
Objectives To determine how, and under what circumstances, the PERFECT-ER intervention was implemented in five acute hospital wards and impacted on staff practices and perceptions.Design Mixed methods process evaluation (undertaken between 2016 and 2018).Setting Five acute hospital wards across three different UK regions.Participants Patients (n=3) admitted to acute wards with hip fracture and cognitive impairment, their relatives (n=29) and hospital staff (n=63).Interventions PERFECT-ER, a multicomponent intervention designed to enhance the recovery of patients with hip fracture and cognitive impairment was implemented for 18 months. PERFECT-ER was implemented at ward level ensuring that multiple new and existing practices were undertaken consistently, on the assumption that collectively, small individual advances would improve care delivery for patients.Primary and secondary outcome measures Implementation of the PERFECT-ER intervention examined through regular intervention scores, service improvement staff reports and action plans, and semi-structured interviews and focus groups.Results The process evaluation identified points of implementation vulnerability and strength. All wards implemented some elements of PERFECT-ER. Implementation was fragile when ward pressures were high and when ward staff perceived the relative priority of intervention practices to be low. Adaptations to the implementation process may have reduced whole-ward staff engagement with implementation. However, strategical enlistment of senior ward influencers (such as ward managers, orthogeriatricians) combined with service improvement lead in-ward peer pressure tactics facilitated implementation processes.Conclusions Our study suggests that implementation was expediated when senior staff were on board as opinion leaders and formally appointed internal implementation leaders exerted their power. Within hierarchical settings such as acute wards, key individuals appeared to influence implementation through endorsement and sometimes enforcement. This indicates that whole-ward interventions may not always require cognitive engagement from all ward staff to implement changes. Future ward-level implementation studies could consider how best to engage staff and most importantly, which staff to best target.Trial registration number ISRCTN99336264.